2015
DOI: 10.1523/jneurosci.3997-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Upregulation of α2δ-1 Subunit Modulates Activity-Dependent Ca2+Signals in Sensory Neurons

Abstract: As auxiliary subunits of voltage-gated Ca 2ϩ channels, the ␣ 2 ␦ proteins modulate membrane trafficking of the channels and their localization to specific presynaptic sites. Following nerve injury, upregulation of the ␣ 2 ␦-1 subunit in sensory dorsal root ganglion neurons contributes to the generation of chronic pain states; however, very little is known about the underlying molecular mechanisms. Here we show that the increased expression of ␣ 2 ␦-1 in rat sensory neurons leads to prolonged Ca 2ϩ responses ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 46 publications
(8 reference statements)
3
46
0
Order By: Relevance
“…We therefore examined the effect of α 2 (3C)δ-1 expressed in cultured DRG neurons on native calcium channel currents (Figure 6c). We have previously shown that expression of WT α 2 δ-1 in cultured DRG neurons caused an increase of native calcium currents (D'Arco et al, 2015) (shown with additional data in Figure 6d). Here, we found that expression of α 2 (3C)δ-1 produced a marked reduction in endogenous calcium channel currents in DRG neurons (by 43.2% at +10 mV; Figure 6c,d), supporting the hypothesis that pro-α 2 δ-1 inhibits endogenous DRG calcium currents.…”
Section: Resultsmentioning
confidence: 67%
“…We therefore examined the effect of α 2 (3C)δ-1 expressed in cultured DRG neurons on native calcium channel currents (Figure 6c). We have previously shown that expression of WT α 2 δ-1 in cultured DRG neurons caused an increase of native calcium currents (D'Arco et al, 2015) (shown with additional data in Figure 6d). Here, we found that expression of α 2 (3C)δ-1 produced a marked reduction in endogenous calcium channel currents in DRG neurons (by 43.2% at +10 mV; Figure 6c,d), supporting the hypothesis that pro-α 2 δ-1 inhibits endogenous DRG calcium currents.…”
Section: Resultsmentioning
confidence: 67%
“…This altered activity results from changes in the properties and/or expression of various types of voltage-gated Na + , K + , and Ca 2+ channels (Waxman et al, 1999;Abdulla andSmith, 2001b, 2002;Cummins et al, 2001;Stemkowski and Smith, 2012b;Bourinet et al, 2014;Waxman and Zamponi, 2014;Daou et al, 2016). There are also changes in the function of Na + -K + ATPases (Venteo et al, 2016), intracellular Ca 2+ handling (Hogan et al, 2014;D'Arco et al, 2015;Yilmaz and Gold, 2016;Yilmaz et al, 2017), TRP channels (Basso and Altier, 2017), and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels (Hogan and Poroli, 2008;Emery et al, 2011;Noh et al, 2014;Young et al, 2014).…”
Section: Mechanisms Of Neuropathic Pain and Potential Therapeuticmentioning
confidence: 99%
“…In the clinical setting, it is also possible that Ca v 2 channel block may have additional long-term consequences, including effects on gene expression, as has been suggested for Na v 1.7 channels (Deuis et al, 2017;Sexton et al, 2017). Effects of Ca v 2 block may be mediated via long-term changes in intracellular Ca 2+ handling by mitochondria (D'Arco et al, 2015). It is also known that nerve injury downregulates HVA calcium channel current (I Ca ) in DRG neurons (Baccei and Kocsis, 2000;Hogan et al, 2000;Abdulla and Smith, 2001b;Pan et al, 2016).…”
Section: Role Of Ectopic Activity In Primary Afferent Fibersmentioning
confidence: 99%
See 2 more Smart Citations